2021
DOI: 10.1097/jcp.0000000000001428
|View full text |Cite
|
Sign up to set email alerts
|

Ayahuasca Improves Self-perception of Speech Performance in Subjects With Social Anxiety Disorder

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 51 publications
4
51
0
Order By: Relevance
“…This case involved a brief but intense moment of disorientation and anxiety, which was resolved with verbal management. 16 The last 3 clinical studies carried out by our research group [4][5][6] (including the manuscript in preparation) gathered a total sample of 56 individuals, including 39 healthy and 17 socially anxious volunteers. Of these, 37 received a single dose of ayahuasca, and only 2 individuals reported a PAR (described here).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This case involved a brief but intense moment of disorientation and anxiety, which was resolved with verbal management. 16 The last 3 clinical studies carried out by our research group [4][5][6] (including the manuscript in preparation) gathered a total sample of 56 individuals, including 39 healthy and 17 socially anxious volunteers. Of these, 37 received a single dose of ayahuasca, and only 2 individuals reported a PAR (described here).…”
Section: Discussionmentioning
confidence: 99%
“…In the placebo group, somnolence (n = 1) was the only event reported. In the trial with socially anxious individuals, 6 a total of 17 adverse effects were reported. In the ayahuasca group, gastrointestinal discomfort and nausea (n = 4), vomiting (n = 3), drowsiness (n = 2), headache (n = 2), diarrhea (n = 1), confusion (n = 2), fear (n = 1), distress (n = 1), and dissociation/depersonalization (n = 1) were reported (the last 4 effects were described in case 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations